Hypertension and diabetes mellitus are not associated with worse renal functional outcome after partial nephrectomy in patients with normal baseline kidney function. (7th October 2018) - Beksac, Alp Tuna; Reddy, Balaji N; Martini, Alberto; Paulucci, David J; Moshier, Erin; Abaza, Ronney; Eun, Daniel D; Hemal, Ashok K; Badani, Ketan K
Abstract : Objective: To analyze the association of hypertension and/or diabetes mellitus on renal function after partial nephrectomy in patients with normal baseline kidney function. Methods: We identified 453 patients with baseline estimated glomerular filtration rate ≥60 that underwent robotic partial nephrectomy for a cT1 renal mass from 2008 to 2014 using a multi‐institutional database. The association between estimated glomerular filtration rate and time (pre‐partial nephrectomy to 24 months post‐partial nephrectomy) was compared between 269 (59.4%) patients with preoperative hypertension and/or diabetes mellitus and 184 (40.6%) patients with neither hypertension nor diabetes mellitus using a multivariable model adjusting for confounders. Results: The estimated glomerular filtration rate significantly decreased over time for both groups compared with baseline (average units/month: 1.8974 hypertension/diabetes mellitus, 1.2163 no hypertension/diabetes mellitus; P  < 0.0001), and the estimated glomerular filtration rate decrease per month reduced over time ( P  < 0.0001). The estimated glomerular filtration rate began to increase at approximately 12 months for the hypertension/diabetes mellitus group, and at approximately 18 months for the no hypertension/diabetes mellitus group. Although a greater initial decline in the estimated glomerular filtration rate after partial nephrectomy was observed for the hypertension/diabetes mellitus group (0.68 units/month), this was not statistically significant ( P  = 0.0842); and while the rate of recovery from this decline was faster for the hypertension/diabetes mellitus group, this also was not statistically significant ( P  = 0.0653). The predicted estimated glomerular filtration rate was similar (83 mL/min/1.73 m 2 ) for both groups 24 months after partial nephrectomy. Conclusions: There seems to be no significant association between hypertension, diabetes mellitus and renal functional outcome after partial nephrectomy in patients with normal baseline glomerular filtration rate. Renal function declines after partial nephrectomy, but then it recovers, irrespective of the presence of hypertension or diabetes mellitus.